A critique of Taiwan's bilingual education policy through a ROAD-MAPPING of teacher experiences. Issue 5 (20th October 2021) - Graham, Keith M.; Pan, W.-Y.; Eslami, Z. R.
ABSTRACT: Bilingual education is spreading throughout the world as an approach for teaching content and language simultaneously. This is particularly true in Taiwan where implementation of bilingual education has begun as directed by the Blueprint for Developing Taiwan into a Bilingual Nation by 2030. However, the spread of bilingual education is often coupled with policies influenced by monolingual ideologies. This collaborative autoethnography critically examines the experiences of two teachers, an American and Taiwanese English teacher, teaching in a bilingual elementary program in Taiwan. Guided by the ROADMAPPING Framework, we critically evaluate our experiences with bilingual education in order to provide a critique of the policy directives for bilingual education implementation in Taiwan. Several issues are addressed including the promotion of monolingual classrooms, the balance of content and language in bilingual education, the use of Western curricula and materials, the hiring of native English speaking teachers (NESTs), and the disconnects and effects that result from the importing of Western practices. From this analysis, we suggest that Taiwan should pursue a glocalized, rather than an internationalized, bilingual education in order to fully achieve its goals of becoming a bilingual nation.